Borderline Personality Disorder. Issue 1 (January 2015) - Zimmerman, Mark
<x xml:space="preserve">Abstract</x> Abstract Compared with bipolar disorder, borderline personality disorder (BPD) is as frequent (if not more frequent), as impairing (if not more impairing), and as lethal (if not more lethal). Yet, BPD has received less than one-tenth the funding from the National Institutes of Health than has bipolar disorder. More than other reviewers of the literature on the interface between bipolar disorder and BPD, Paris and Black (Paris J and Black DW (2015) Borderline Personality Disorder and Bipolar Disorder: What is the Difference and Why Does it Matter? J Nerv Ment Dis 203:3–7) emphasize the clinical importance of correctly diagnosing BPD and not overdiagnosing bipolar disorder, with a focus on the clinical feature of affective instability and how the failure to recognize the distinction between sustained and transient mood perturbations can result in misdiagnosing patients with BPD as having bipolar disorder. The review by Paris and Black, then, is more of an advocacy for BPD than other reviews in this area have been. In the present article, the author will illustrate how the bipolar disorder research community has done a superior job of advocating for and "marketing" their disorder compared with researchers of BPD. Specifically, researchers of bipolar disorder have conducted multiple studies highlighting the problem with underdiagnosis, written commentaries about the problem with underdiagnosis, developed and promoted several screening scales to improve diagnostic recognition, published numerous studies of the operating characteristics of these screening measures, attempted to broaden the definition of bipolar disorder by advancing the concept of the bipolar spectrum, and repeatedly demonstrated the economic costs and public health significance of bipolar disorder. In contrast, researchers of BPD have almost completely ignored each of these issues and thus have been less successful in highlighting the public health significance of the disorder.